Legal Issues of Eliminating Electronic Contracts in E Commerce Transactions: A Digital Consumer Protection Perspective - Adelia Vega; Annisa Husna Nst; Putri Rohmaito Tinambunan; Mursyida Thohir (Jurnal Sahabat ISNU SU, 2025)
The development of digital technology has transformed transaction patterns from conventional systems to platforms.e-commerce, creating new challenges in the legal aspects related to the cancellation or termination of electronic contracts, which impacts consumer protection in the digital era. This study examines in depth the legal complexities in the context of terminating electronic contracts in transactions.e-commerce, with a specific focus on consumer protection aspects in Indonesia's digital environment. The research was conducted using a normative juridical methodology, integrating legislative and conceptual approaches, relying on analysis of secondary data covering primary, secondary, and tertiary legal materials. The research findings reveal distinctive characteristics in the termination of electronic contracts in the digital realm.e-commerce compared to traditional contracts, particularly in terms of evidence and conflict resolution. This study identifies gaps in the existing regulatory framework, where digital consumer protection has not been optimally accommodated in the context of electronic contract termination, indicating the urgency of implementing regulatory updates that are more responsive to the dynamics of digital technology